2022
DOI: 10.1002/er.8551
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous cobalt boride nanoparticles incorporated vanadium carbide MXene composite for asymmetric supercapacitor applications

Abstract: Summary The use of novel, low‐cost, and efficient electrode materials in high‐power energy technology is highly anticipated for the development of user‐friendly products. Recently, “MXenes” have been identified as a novel class of advanced two‐dimensional (2D) layered transition metal compounds that have piqued the interest of researchers in a variety of electrochemical applications due to their remarkable physicochemical properties that resemble other 2D materials such as graphene. Similarly, an amorphous tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…The assembled composite HSC showed a power density of 800 W/kg and energy density of 31.5 Wh/kg and was still capable of maintaining a specific energy of 14.4 Wh/kg @ 4 kW/kg. In addition, the device demonstrated exceptional cyclic stability with a retention of 89.2 % after 2500 charge‐discharge cycles [88] …”
Section: Vanadium Carbide Mxene As Supercapacitormentioning
confidence: 99%
See 3 more Smart Citations
“…The assembled composite HSC showed a power density of 800 W/kg and energy density of 31.5 Wh/kg and was still capable of maintaining a specific energy of 14.4 Wh/kg @ 4 kW/kg. In addition, the device demonstrated exceptional cyclic stability with a retention of 89.2 % after 2500 charge‐discharge cycles [88] …”
Section: Vanadium Carbide Mxene As Supercapacitormentioning
confidence: 99%
“…In addition, the device demonstrated exceptional cyclic stability with a retention of 89.2 % after 2500 charge-discharge cycles. [88] The binder-free films made from MXene hetero-layers exhibit better performance and surprising electrochemical characteristics with higher volumetric capacitance. Vahid Mohammadi et al have demonstrated negatively charged, self- EIS plots (e) cyclic performance @ 10 A g À 1 and inset super-capacitor schematic.…”
Section: Vanadium Carbide Mxene As Supercapacitormentioning
confidence: 99%
See 2 more Smart Citations
“…AlB 2 -type metal borides are primarily ionic layered materials, where adjacent layers are held together by ionic bonding. , This structure gives rise to a number of interesting properties, including ultrahigh strength, good electrical and thermal conductivity, wear resistance, chemical inertness, and high melting point. , MgB 2 , the flagship member of the metal diboride family, is known for its superconductivity, TiB 2 is known for its use in ballistic armors, and AlB 2 has been used as a reinforcing material. , However, they are recently being revisited in multiple new domains due to their excellent electrochemical properties. One of the earliest reports highlighted the investigation of various metal diborides such as AlB 2 , CrB 2 , HfB 2 , MgB 2 , NbB 2 , TaB 2 , TiB 2 , VB 2 , and ZrB 2 as potential catalysts for HER, VB 2 and WB 2 for batteries, and MgB 2 for water splitting and lithium-ion batteries. ,, Research trends in the synthesis of metal diborides encompass various methods including the solid-state reaction method, sol–gel synthesis, mechanical alloying, and self-propagating high-temperature synthesis (SHS). These techniques allow for precise control over material properties, microstructure, and phase composition, offering tailored metal diborides for specific applications.…”
Section: Research Trends In Alb2-type Metal Diborides and Xbenesmentioning
confidence: 99%